2020
DOI: 10.1590/1678-992x-2018-0247
|View full text |Cite
|
Sign up to set email alerts
|

Methane mitigation and ruminal fermentation changes in cows fed cottonseed and vitamin E

Abstract: Inherently, ruminant production of methane (CH 4), a greenhouse gas (GHG), causes animal energy losses. Cottonseed is a lipid source and is used sometimes to enhance energy density in cattle diets. It also can mitigate enteric CH 4. Lipids release peroxides in the rumen, and antioxidants have the ability to neutralize them. Thus, a lipid and antioxidant source can benefit rumen fermentation. The aim of this study was to evaluate rumen fermentation parameters from cows fed cottonseed and vitamin E. Six cannulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In contrast, Duthie et al (2018) did not find significant differences in enteric CH 4 production in steers fed increasing amounts of dietary lipid sourced from maize distillers dark grains, which increased diet ether extract from 24 to 37 g/kg DM for 17 weeks. Supplementation of diets with cottonseed oil has been shown to decrease enteric CH 4 production by~42% (Nogueira et al 2020). These authors suggested that bio-hydrogenation of lipids served as an alternative H 2 sink, and with each percentage point of lipid added to the diet, CH 4 production was reduced by 8%.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…In contrast, Duthie et al (2018) did not find significant differences in enteric CH 4 production in steers fed increasing amounts of dietary lipid sourced from maize distillers dark grains, which increased diet ether extract from 24 to 37 g/kg DM for 17 weeks. Supplementation of diets with cottonseed oil has been shown to decrease enteric CH 4 production by~42% (Nogueira et al 2020). These authors suggested that bio-hydrogenation of lipids served as an alternative H 2 sink, and with each percentage point of lipid added to the diet, CH 4 production was reduced by 8%.…”
Section: Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…The reduction in acetate over time after supplementation likely occurred as it is a substrate for the production of butyrate via the inverse β-oxidase pathway [49], which also explains the decrease in the acetate:propionate ratio. Nogueira et al [50] observed a similar response in ruminal parameters of cows fed with cottonseed in the successive hours after supplementation (0 to 12 h), where acetate decreased between 3 and 6 h after supplementation, and propionate had a slight increase between 0 and 3 h, and after 3 h remained constant until 12 h after supplementation.…”
Section: Ruminal Parametersmentioning
confidence: 65%
“…Estimated methane emissions in grazing cows in this study reduced linearly according to CO inclusion level in the diet, with the highest inclusion reducing nearly 17% daily methane output. Several studies have reported that lipids reduce CH 4 production in the rumen by different mechanisms (Dohme et al, 2001 ; Machmüller et al, 2001 ; Bayat et al, 2018 ; Muñoz et al, 2019 ; Nogueira et al, 2020 ). Similar to our findings, Moate et al ( 2011 ) showed that lactating cows’ diets (60:40 ratio of forage: concentrate) containing 51, 52, and 65 g fat/kg DM decreased emissions of CH 4 (g/day) in a linear fashion (7.6, 4.5 and 10.2%, respectively), compared to a control diet.…”
Section: Discussionmentioning
confidence: 99%